2008
DOI: 10.1007/s00702-008-0083-y
|View full text |Cite
|
Sign up to set email alerts
|

Increased EEG gamma band activity in Alzheimer’s disease and mild cognitive impairment

Abstract: High frequency (30-70 Hz) gamma band oscillations in the human electro-encephalogram (EEG) are thought to reflect perceptual and cognitive processes. It is therefore interesting to study these measures in cognitive impairment and dementia. To evaluate gamma band oscillations as a diagnostic biomarker in Alzheimer's disease (AD) and mild cognitive impairment (MCI), 15 psychoactive drug naïve AD patients, 20 MCI patients and 20 healthy controls participated in this study. Gamma band power (GBP) was measured in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
118
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(127 citation statements)
references
References 39 publications
8
118
1
Order By: Relevance
“…Previous EEG (Babiloni et al 2004;Dauwels et al 2011;Huang et al 2000;Jeong 2004) and MEG studies (Berendse et al 2000;Fernandez et al 2002Fernandez et al , 2003Fernandez et al , 2006b) of AD found an increased power in the low-frequency bands (delta and theta), accompanied by a decreased power in the high-frequency range (alpha, beta, and gamma). Such pattern of spectral changes is a consistent finding that correlates with cognitive performance and functional status (Fernandez et al 2002;Prichep et al 1994;van Deursen et al 2008). …”
Section: Discussionsupporting
confidence: 53%
“…Previous EEG (Babiloni et al 2004;Dauwels et al 2011;Huang et al 2000;Jeong 2004) and MEG studies (Berendse et al 2000;Fernandez et al 2002Fernandez et al , 2003Fernandez et al , 2006b) of AD found an increased power in the low-frequency bands (delta and theta), accompanied by a decreased power in the high-frequency range (alpha, beta, and gamma). Such pattern of spectral changes is a consistent finding that correlates with cognitive performance and functional status (Fernandez et al 2002;Prichep et al 1994;van Deursen et al 2008). …”
Section: Discussionsupporting
confidence: 53%
“…Thus increased callosal white matter, which implies increased callosal myelination, reflects an enhanced facilitation of neural transmission und consequently facilitated and more efficient synchronization of neural activity between the two hemispheres. Interestingly, analogous correspondence between dysfunctional neural connectivity and altered oscillatory gamma activity has been reported in schizophrenia (Wilson et al, 2008;Herrmann and Demiralp, 2005;Lenz et al, 2011), as well as in Alzheimer's disease (He et al, 2009;van Deursen et al, 2008). However, so far the majority of these studies focused on the pathological related amplitudinal alterations of GBR.…”
Section: Discussionmentioning
confidence: 83%
“…One of the major effects is EEG "slowing"; many studies have shown that Mild Cognitive Impairment (MCI) and Alzheimer's disease (AD) causes EEG signals to slow down (see, e.g., [52,53,54,55,56,57,58,59,60,61,62,63,64,65]): MCI/AD is associated with an increase of power in low frequencies (delta and theta band, 0.5-8Hz) and a decrease of power in higher frequencies (alpha and beta, 8-30Hz). However, increased gamma band power (30-100Hz) has been reported in MCI/AD patients compared to healthy age-matched control subjects [67].…”
Section: Slowing Of Eegmentioning
confidence: 99%